Analyzing epigenetic control of galectin expression indicates silencing of galectin-12 by promoter methylation in colorectal cancer - Katzenmaier, Eva-Maria Katharina; Kloor, Matthias; Gabius, Hans-Joachim; Gebert, Johannes; Kopitz, Jürgen (IUBMB life, 2017)
Galectins, a class of lectins with specificity for ß-galactoside containing glycoconjugates, modulate several cellular processes that are involved in the control of normal cell growth, differentiation, cell-cell, and cell matrix interactions. Pathological alterations of the galectin expression pattern have been implicated in the development and progression of cancer. We therefore analyzed epigenetic mechanisms for control of galectin expression in 9 colorectal cancer (CRC) cell lines. Our data demonstrate that expression of galectins-1, −2, −7, −8, and −9 can be regulated by histone acetylation in CRC cell lines. In addition, the same set of galectins was also found to be modulated by DNA methylation. Of particular note, galectin-12 is silenced in all tested CRC cell lines but known to be re-expressed upon butyrate-induced differentiation and present in normal colonic mucosa. Loss of galectin-12 expression in undifferentiated CRC cells is associated with promoter hypermethylation and for the first time we provide detailed methylation analysis of the promoter region. In CRC tumor tissue, galectin-12 expression was downregulated in 66% of CRC tissue specimens as compared to adjacent normal tissue hinting to a possible tumor-suppressing function in CRC. © 2017 IUBMB Life, 69(12):962-970, 2017